A pilot randomised controlled trial of a preconsultation web-based intervention to improve the care quality and clinical outcomes of diabetes outpatients (DIAT). Issue 7 (31st July 2013) - Frost, Julia; Anderson, Rob; Argyle, Catherine; Daly, Mark; Harris-Golesworthy, Faith; Harris, Jim; Gibson, Andy; Ingram, Wendy; Pinkney, Jon; Ukoumunne, Obioha C; Vaidya, Bijay; Vickery, Jane; et al.
Abstract : Introduction: Diabetes is a chronic condition associated with many long-term complications. People with diabetes need to actively manage their condition, which can be complex. In consultations with healthcare professionals, patients receive advice about their diabetes but do not always discuss things which concern them, perhaps because of the perceived limited time or embarrassment. We want to test a 'preconsultation' intervention in which the patient is supported by a healthcare assistant to complete a web-based intervention aimed at producing an agenda to help them identify important areas for discussion in the consultation. Use of this agenda may enable the patient to play a more active role in that consultation and consequently become more confident, and hence more successful, in managing their condition. Methods and analysis: In this pilot randomised controlled trial, 120 people with diabetes will be randomised with equal allocation to receive the intervention or usual clinical care. The primary outcome is reduction in glycosylated haemoglobin(HbA1c). Secondary outcomes are patient-reported communication, enablement, self-care activity, diabetes-dependent quality of life, empowerment, satisfaction, health-related quality of life and resource use. The aim of the pilot study was to estimate parameters to inform the design of the definitive trial. Follow-up on quantitative outcomes will be at 3 and 6 months. A nested qualitative study will collect data on the patients' experiences of producing an agenda. Resource use data and medication use will also be collected via a review of medical records for a sample of participants. Ethics and dissemination: Approval was granted by the NHS Research Ethics Committee North West—Preston (13/NW/0123). Dissemination will include publication of quantitative and qualitative findings, and experience of public involvement in peer-reviewed journals. Results will also be disseminated to trial participants via workshops led by lay coapplicants. Trial Registration: ISRCTN75070242.